VIOLATION OF HUMAN RIGHTS OF OLDER PERSONS IN SOUTH AFRICA. THE CASE OF LAVELA OLD AGE CENTRE, NTSELAMANZI, EASTERN CAPE PROVINCE, SOUTH AFFRICA - Kang’ethe, Simon (Social Work/Maatskaplike Werk, 2018)
There is no doubt that older persons face an environment bereft of resources, rights and dignity. This study was explorative and descriptive in design, with data collected from in-depth discussions with the elderly. Findings revealed diametrically opposed factors, with some older persons happily accessing an array of psychosocial benefits, while some had their grants mishandled or complained of the inadequacy of the grant. Others felt their rights to housing were largely being compromised. This paper recommends that the government prioritise the older persons’ state of housing and provide funding for old age centres to ensure that they become sources of psychosocial benefit for elderly members of society.